Decreased Speech-In-Noise Understanding in Young Adults with Tinnitus - Gilles, Annick; Schlee, Winny; Rabau, Sarah; Wouters, Kristien; Fransen, Erik; Van de Heyning, Paul (Frontiers in Neuroscience, 2016)
Objectives. Young people are often exposed to high music levels which make them more at risk to develop noise-induced symptoms such as hearing loss, hyperacusis and tinnitus of which the latter is the symptom perceived the most by young adults. Although subclinical neural damage was demonstrated in animal experiments, the human correlate remains under debate. Controversy exists on the underlying condition of young adults with normal hearing thresholds and noise-induced tinnitus due to leisure noise. The present study aimed to assess differences in audiological characteristics between noise-exposed adolescents with and without noise-induced tinnitus (NIT). Methods. A group of 87 young adults with a history of recreational noise exposure was investigated by use of the following tests: otoscopy, impedance measurements, pure-tone audiometry including high-frequencies, transient and distortion product otoacoustic emissions, speech-in-noise testing with continuous and modulated noise (amplitude-modulated by 15Hz), auditory brainstem responses (ABR) and questionnaires. Nineteen students reported NIT due to recreational noise exposure, and their measures were compared to the non-tinnitus subjects. Results. No significant differences between tinnitus and non-tinnitus subjects could be found for hearing thresholds, otoacoustic emissions and ABR results. Tinnitus subjects had significantly worse speech reception in noise compared to non-tinnitus subjects for sentences embedded in steady-state noise (mean speech reception threshold (SRT) scores respectively -5.77 dB SNR and -6.90 dB SNR; p = 0.025) as well as for sentences embedded in 15 Hz AM-noise (mean SRT scores respectively -13.04 dB SNR and -15.17 dB SNR; p = 0.013). In both groups speech reception was significantly improved during AM-15Hz noise compared to the steady-state noise condition (p < 0.001). However, the modulation masking release was not affected by the presence of NIT. Conclusions. Persons with and without NIT did not differ regarding audiometry, OAE and ABR. However, tinnitus patients showed decreased speech-in-noise reception. The results are discussed in the light of previous findings suggestion noise-induced tinnitus may occur in the absence of measurable peripheral damage as reflected in speech-in-noise deficits in tinnitus subjects.